The Effect of Accounting Information System Payroll and Internal Control to The Performance of Employees - Evi Violina (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study examines the effect of accounting information systems payroll and internal control on employee performance. Data regarding accounting information system payroll, internal control, employee performance were obtained through questionaires to employees of PT Oasis Waters International Cabang Bandung. The data obtained were then analyzed using multiple linier regression analysis methods, and using SPSS. The results showed that there was an influence between the accounting information system payroll (X1) and internal control (X2) on employee performance (Y).